Silicon carbide power devices - Brligr, B. Jayant; Brligr, B. Jayant (World Scientific Publishing Co. Pte. Ltd, 2006)
Power semiconductor devices are widely used for the control and management of electrical energy. The improving performance of power devices has enabled cost reductions and efficiency increases resulting in lower fossil fuel usage and less environmental pollution.